Operability of atrial septal defect with borderline pulmonary vascular resistance index: A study in developing country - Lilyasari, Oktavia; Istisakinah, Rini; Ariani, Rina; Rahmat, Budi; Liastuti, Lies Dina; Kurniawati, Yovi; Muliawan, Hary Sakti; Sukmawan, Renan (Frontiers in Surgery, 2022)
Background: Pulmonary arterial hypertension secondary to atrial septal defect is an important determinant of morbidity and mortality in defect closure. This study is aimed to compare perioperative outcome of preoperative borderline (> 4 WU.m2) and low (<4 WU.m2) PVRI in surgical closure of secundum atrial septal defect with concomitant pulmonary arterial hypertension. Methods and Results: This was a single-centre retrospective cohort study between January 2015 and January 2020. We classified patients with low and borderline PVRI who underwent ASD closure and recorder the perioperative outcomes. Results: We analysed a total of 183 patients with atrial septal defect and pulmonary arterial hypertension; 92 patients with borderline PVRI and 91 patients with low PVRI. Borderline pulmonary vascular resistance index was not associated with increased risk of postoperative mortality (p=0.621; OR0.48, 95% CI 0.04-5.48), but associated with higher risk of overall morbidity in bivariate analysis (p=0.002; OR3.28, 95% CI 1.5-6.72). Multivariate analysis showed positive association of borderline pulmonary vascular resistance index (p=0.045; OR2.63, 95%CI 1.02-6.77) and preoperative tricuspid valve gradient > 64 mmHg (p=0.034; OR2.77, 95%CI 1.08-7.13) with overall morbidity. Conclusion: There is no difference in incidence of in-hospital mortality between preoperative borderline and low pulmonary vascular resistance index patients. However, preoperative borderline pulmonary vascular resistance index and tricuspid valve gradient > 64mmHg are associated with increased overall morbidity after surgical closure in secundum atrial septal defect patients with pulmonary arterial hypertension.